Brunei Darussalam : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This report describes economic developments in Brunei Darussalam during the 1990s. During 1994-95, domestic demand picked up strongly mainly owing to the rise in government expenditure. As the government accelerated the implementation of key projects in the Sixth National Development Plan, large community-oriented projects were also implemented. The increase in investment spending and associated consumption boom resulted in a sharp growth in imports and a significant rise in inflation. In the meantime, broad money continued to expand rapidly as substantial funds were brought into the banking system from abroad to finance major development projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet